Potential of Rhizopus delemar and Rhizopus microsporus as tempeh starters - ANASTASIA T. HARTANTI; BAGAS CRISTANTO KURNIAWAN; AGUSTIN WYDIA GUNAWAN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Hartanti AT, Kurniawan BC, Gunawan AW. 2024. Potential of Rhizopus delemar and Rhizopus microsporus as tempeh starters. Biodiversitas 25: 4208-4214. The biodiversity of tempeh-associated Rhizopus in Indonesia has decreased due to the widespread use of commercial starters. This study aimed to conserve three pure Rhizopus strains (Rhizopus delemar ATH 53, R. microsporus ATH 1 and ATH 24) of tempeh starters and optimize their use in tempeh production. Using rice flour and Rhizopus spores at 106/mL concentration, tempeh starters were made and stored for up to 12 weeks, maintaining spore viability at 106/g with 7-14% water content. Tempeh production experiments utilized three starter doses (0.1, 0.2, 0.3 g per 100 g soybeans) and three different incubation temperatures (27, 30, and 35°C), all of which successfully yielded tempeh. Sensory evaluations revealed that ATH 1 and ATH 53 starters were superior over ATH 24, which produced a distinct yellow tempeh that sporulated easily. It was also noted that 0.1 g of starter per 100 g of soybeans was sufficient for producing high-quality tempeh, offering an efficient use of starter. By successfully conserving these Rhizopus strains as viable tempeh starters for at least 12 weeks, results of present study demonstrate a promising approach to maintaining biodiversity in Indonesian tempeh production, paving the way for further exploration of traditional Rhizopus strains in tempeh making.